Colleges and schools-College of Agricultural Sciences and Technology-Viticulture and Enology 106
Don Bavaro, lecturer, and Vincent Petruicci, professor of viticulture, received a $1,000 check from Lucy Milla and Elaine Gunland of the Raisin Wives of California. Mrs. Milla, of Rolinda, is a former vice president and program chairman of the Raisin Wives and Mrs. Gunland, is the Easton-Caruthers area, is the current president of the group. Gathered around for the presentation are members of Petrucci's class in raisin production, which is part of the viticulture program offered through the School of Agriculture and Home Economics at California State University, Fresno. When he was an Undergraduate, Bavaro was one of the first recipients of the Raisin Wives scholarship. Petrucci said receipients of this year will be announced later.